Histopathological study of tapeworm infection in Mastacembalus armatus from Sina Kolegoan dam Osmanabad dist. (MS). - Jadhav, Swati; Borde, Sunita; Jadhav, Dilip; Humbe, Atul (Journal of Experimental Sciences, 2012)
The histopathological study of the parasitized tissues of fishes of Sina Kolegoan dam was undertaken. The fish Mastacembalus armatus (Lecepede,1800) examined for gastrointestinal parasitic infections are Ptychobothridian cestode, Circumoncobothrium osmanabadensis. The histopathology of the fish tissues shows different pathological conditions. Histopathological study has been made to assess the extent of damage caused by the parasite. Histological changes include destruction and extrusion of the intestinal villi, fibroblast cell and plasma cell. It seems that the environment of the intestine is quite favourable for the worm Circumoncobothrium osmanabadensis.So the worm finds it easy to absorb the same through tegument for growth and nourishment.